Arthroscopic treatment of isolated subscapolaris lesions: our experience - Mancuso, F.; Di Benedetto, P.; Beltrame, A.; Cainero, V.; Causero, A. (Acta Biomedica Atenei Parmensis, 2014)
Background and aim of the work: Subscapularis tendon lesions, in particular the isolated ones, are often not recognized and undervalued, so in theliterature they are described with a variable incidence. Aim of the work is presenting our experience with the short to medium term follow up results of the arthroscopic repair of isolated subscapularis lesions. Methods: We retrospectively analyzed 311 shoulder arthroscopies performed by a single senior surgeon, from which we have found 10 isolated subscapularis lesions. After the arthroscopic repair of subscapularis tendon the patients have been evaluated with a median follow up of 17.7 months with specific tests for the subscapularis (Napoleon’s and lift off tests) and clinical scores (Constant and UCLA scores). Results:We have obtained the tests negativization with an internal rotation level up to D8. The Constant score reached 86.7 with a median improvementof 49.4 points. The UCLA score at the last follow up was 30.8 with a median improvement of 20.1 points. Conclusions: Isolated subscapularis lesions are uncommon and often they are not correctly diagnosed. Arthroscopy has a decisive role in both the diagnostic and therapeutic side, with good short to medium term results.